Regulatory effects of marine polysaccharides on gut microbiota dysbiosis: A review - Jieying Ou; Zhuo Wang; Xiaofei Liu; Bingbing Song; Jianping Chen; Rui Li; Xuejing Jia; Riming Huang; Wenzhou Xiang; Saiyi Zhong (Food Chemistry: X, 2022)
The gut microbiota dysbiosis is a state which the physiological combinations of flora are transformed into pathological combinations caused by factors such as diets, pollution, and drugs. Increasing evidence shows that dysbiosis is closely related to many diseases. With the continuous development and utilization of marine resources, marine polysaccharides have been found to regulate dysbiosis in many studies. In this review, we introduce the types of dysbiosis and the degree of it caused by different factors. We highlight the regulating effects of marine polysaccharides on dysbiosis as a potential prebiotic. The mechanisms of marine polysaccharides to regulate dysbiosis including protection of intestinal barrier, regulatory effect on gut microbiota, alteration for related metabolites, and some other possible mechanisms were summarized. And we aim to provide some references for the high-value utilization of marine polysaccharides and new targets for the treatment of gut microbiota dysbiosis by this review.